2013
DOI: 10.1128/jvi.01773-13
|View full text |Cite
|
Sign up to set email alerts
|

The Current Hepatitis C Virus Prevalence in China May Have Resulted Mainly from an Officially Encouraged Plasma Campaign in the 1990s: a Coalescence Inference with Genetic Sequences

Abstract: In this study, we investigated hepatitis C virus (HCV) molecular epidemiology and evolutionary dynamics. Both E1 and NS5B sequences were characterized in 379 of 433 patients in southern China and classified into five major subtypes: 1b in 256 patients, 6a in 67 patients, 2a in 29 patients, 3a in 14 patients, and 3b in 13 patients. Using the E1 sequences obtained, along with those from other studies using samples from China, we inferred the HCV epidemic history by means of coalescence strategies. Five Bayesian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 41 publications
3
24
2
Order By: Relevance
“…This corresponds to a period during which contaminated blood transfusions were common, largely due to a procedural error in an officially encouraged plasma campaign. Using a parametric model, we estimated the HCV population growth rates during this period and suggested that certain barriers to efficient viral transmission were removed, allowing nationwide dissemination (20). Although these findings support the belief that the plasma campaign founded the high HCV prevalence in China, the current HCV genotype distribution patterns could also have been affected by subsequent human migrations.…”
mentioning
confidence: 40%
“…This corresponds to a period during which contaminated blood transfusions were common, largely due to a procedural error in an officially encouraged plasma campaign. Using a parametric model, we estimated the HCV population growth rates during this period and suggested that certain barriers to efficient viral transmission were removed, allowing nationwide dissemination (20). Although these findings support the belief that the plasma campaign founded the high HCV prevalence in China, the current HCV genotype distribution patterns could also have been affected by subsequent human migrations.…”
mentioning
confidence: 40%
“…Four clusters were identified. Clusters I, II, and III are the same as those we have reported previously [13,15,17,30], each having a full posterior probability of 1.00. In contrast, the fourth cluster is not as robust as these three; it has a probability of only 0.51 and is thus unnamed.…”
Section: Subtype 6amentioning
confidence: 51%
“…Surprisingly, this time frame was much later than that we estimated for other HCV subtypes. Although we should bear in mind that the time frames of other HCV subtypes correspond to a period during which a procedural error occurred in an officially encouraged plasma campaign in China [17], a delayed time frame for subtype 1a may indicate its unique epidemic history. A better interpretation was provided by a BSP, which estimated the rapid population growth of subtype 1a occurred during 1998~2005.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations